Investigating the use of potassium-rich pellet on the feed conversion ratio, water quality analysis and fruit development of lycopersicon sp. growing in aquaponics system - Hilmi, Kamaludin (2017)
Title of my thesis is investigating the use of potassium-rich pellet on the feed conversion ratio, water quality analysis and fruit development of Lycopersicon sp. growing in aquaponics.Main objective is to develop the suitable production for potassium-rich pellet that contain balanced nutritional value, to investigate the capability of potassium-rich pellet to increasing the fruit development and flowering in aquaponics system and investigate the Feed Conversion Ratio (FCR) when given the potassium-rich pellet compared to commercial pellet. In this thesis, the experiment conducted about 90 days. The chlorophyll content inside the leaves was determined and the water quality analysis was conducted consist of dissolved oxygen (DO), pH, salinity, Electrical Conductivity (E.C) and Total Dissolved Solids (TDS). Also, the fish weight and calculation of FCR were conducted. The result shows that the commercial pellet have more nutrient and capable of making flowering and ripening of tomato compared to the potassium-rich pellet.